Shear resistance of an auxetic chiral mechanical metamaterial. (10th November 2019) - Jin, Shengguang; Korkolis, Yannis P.; Li, Yaning
Abstract: The shear resistance of 3D printed periodic auxetic chiral mechanical metamaterial was quantified via a picture-frame apparatus. The experimental set-up allowed the accurate measurement of the effective shear modulus of the material. Also, a rigid-rod-rotational spring model shows that the effective shear modulus of the material is directly related to the chiral geometry and the rotational rigidity of the center joints and the corner joints in the chiral cell. To facilitate practical design, design guidelines were developed through an integrated analytical, numerical and experimental approach. The influences of the chiral geometry and the joint rigidity on the shear resistance of the periodic auxetic chiral mechanical metamaterial were quantified. The design guidelines were verified by systematic finite element (FE) simulations.